Analisis Faktor Penyebab Penumpukan Pencairan Dana APBN pada Akhir Tahun Anggaran - Fandi Zaenudinsyah (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2016)
Central government expenditures as the largest component of state expenditures have an important role in determining national output and affecting allocation and efficiency of economic resources. The increase of state expenditures, both for central government expenditures and transfer to local governments, are ideally followed by responsive budget absorption pattern. The high remaining budget at the end of the year indicates that the budget implementation is not optimal, which could lead to economic losses. This low budget absorption pattern has also occurred at the spending units at the State Treasury Service Office (KPPN) Jakarta V. This study aims to determine the factors that cause a low budget absorption pattern of the state budget (APBN) at the end of the fiscal year at KPPN Jakarta V. This study used method of data analysis in the form of factor analysis. The results show that the low budget absorption pattern of the state funds at the end of the fiscal year is caused by eight factors, namely treasury administration, procurement implementation, budget planning, technical support requirements, procurement schedule, human resources, competencies, and job rotation. This study uses method of data analysis in the form of factor analysis. The results showed that the buildup of disbursement of state funds by the end of the fiscal year at the working units within KPPN Jakarta V caused by the eight factors, namely the treasury administration, procurement implementation, planning, supporting technical requirement, procurement scheduling, human resources, competencies, and mutation of officers in charge. Abstrak Belanja pemerintah pusat sebagai komponen terbesar belanja negara memiliki peran penting dalam menentukan output nasional dan mempengaruhi alokasi dan efisiensi sumber daya ekonomi. Peningkatan belanja negara, baik belanja pemerintah pusat maupun transfer ke daerah, idealnya diikuti dengan pola penyerapan yang responsive. Penyerapan anggaran yang masih menumpuk pada akhir tahun mengindikasikan bahwa pelaksanaan anggaran belum optimal, bahkan dapat menyebabkan kerugian negara secara ekonomis. Penumpukan pencairan dana tersebut juga terjadi pada Satuan Kerja lingkup Kantor Pelayanan Perbendaharaan Negara (KPPN) Jakarta V. Penelitian ini bertujuan untuk mengetahui faktor-faktor penyebab penumpukan pencairan dana APBN pada akhir tahun anggaran. Penelitian ini menggunakan metode analisis data berupa analisis faktor. Hasil penelitian menunjukkan bahwa penumpukan pencairan dana APBN pada akhir tahun anggaran pada Satuan Kerja lingkup KPPN Jakarta V disebabkan oleh delapan faktor, yaitu administrasi perbendaharaan, pelaksanaan pengadaan, perencanaan anggaran, persyaratan teknis pendukung, jadwal pengadaan, sumber daya manusia, kompetensi, dan mutasi pejabat.